Anisotropy Analysis of the Permeation Behavior in Carbon Dioxide-Assisted Polymer Compression Porous Products - Takafumi Aizawa (Technologies, 2023)
The carbon dioxide-assisted polymer compression method is used to create porous polymer products with laminated fiber sheets that are crimped in the presence of carbon dioxide. In this method, fibers are oriented in the sheet-spread direction, and the intersections of the upper and lower fibers are crimped, leading to several intersections within the porous product. This type of orientation in a porous material is anisotropic. A dye solution was injected via a syringe into a compression product made of poly(ethylene terephthalate) nonwoven fabric with an average fiber diameter of 8 μm. The anisotropy of permeation was evaluated using the aspect ratio of the vertical and horizontal permeation distances of a permeation area. The aspect ratio decreased monotonically with decreasing porosity; it was 2.73 for the 80-ply laminated product with a porosity of 0.63 and 2.33 for the 160-ply laminated product with a porosity of 0.25. A three-dimensional structural analysis using X-ray computed tomography revealed that as the compression ratio increased, the fiber-to-fiber connection increased due to the increase in adhesion points, resulting in decreased anisotropy of permeation. The anisotropy of permeation is essential data for analyzing the sustained release behavior of drug-loaded tablets for future fabrication.